The damselfly genus Mecistogaster (Odonata: Pseudostigmatidae) from the Brazilian Atlantic Forest with a description of three new species and a neotype designation for M. amalia (Burmeister, 1839) - Lacerda, Déborah S. Soldati; Machado, Angelo B. Monteiro (Zootaxa, 2019)
Mecistogaster Rambur, 1842 is a genus of Pseudostigmatidae with five species distributed from Mexico to Argentina. Four of these occur in Brazil, two of which were recorded on the Atlantic Forest, M. amalia (Burmeister, 1839) and M. linearis (Fabricius, 1776). After examining 140 specimens of Mecistogaster amalia it was possible to conclude that it is a complex of species and three new species are described, M. kesselringi sp. nov., M. mielkei sp. nov. and M. nordestina sp. nov. The males differ from each other mainly by the presence or absence of alula, the area occupied by the reddish-brown color of the mesepimeron and penis structure. The females differ mainly by the region occupied for the pale apical area of wing and epiproct shape. The problem of Burmeister’s type of M. amalia is discussed and a neotype is erected for it. Distribution and phenology data are provided. A key for males recorded from Brazilian Atlantic Forest is presented.